Analisis Kejadian Stunting di Desa Serut - Zuhrotul Eka Yulis Anggraeni; Eli Rahmatika Nugrahani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Prevalence data for stunting in East Java in 2022 is 32.8% higher than national data (Wardita, Suprayitno and Kurniyati, 2021). This condition also has an impact on coverage figures based on Jember district, which is one that has high stunting rates for both toddlers and toddlers. Jember has 35 stunting loci. The purpose of this study was to find out which dominant factors influence the incidence of stunting. The research design used is case control. The population that has a risk of 106 samples taken as many as 60 with the random sample method. 30 cases 30 controls. The instrument used is a questionnaire that reflects the dominant factors in the incidence of stunting. The variables of this study are the number of children, exclusive breastfeeding, eating problems, health problems, history of pregnancy and health services. The results obtained based on test analysis show that the most dominant factor influencing the incidence of stunting in the Serut Village is a history of unfavorable pregnancies and health problems for children who are often sick.